Is There a Sociologist in the Room? Raising the Sociological Voice in Educational Spaces - Alfi-Nissan, Sari R. (Qualitative Sociology Review, 2025)
Educational spaces are both material and human sites. While people design and build the physical space of educational institutions, these spaces also shape human behavior, interaction, and thought, playing a crucial role in the articulation of discourse. Critical Discourse Analysis (CDA) in educational research tends to rely primarily on document and text analysis, often overlooking the spatial dimensions of discourse and how social actors interpret the spaces they inhabit. This article presents the use of semiotic codes analysis of educational spaces as a methodological tool for studying discourse in institutions where ethnographic access is limited. Drawing on a qualitative study conducted in twelve Israeli state schools, this article examines how global discourses of entrepreneurialism and aspiration, which promote an ideal of a future-oriented and self-managing individual, are expressed and interpreted in everyday school settings. Through observations, walking interviews, and semiotic analysis, the study demonstrates how spatial articulations, wall texts, and visual displays work together with educators’ interpretations to shape and sometimes contest dominant ideals. The analysis merges critical spatial semiotics with a pragmatic approach to everyday meaning-making, offering a methodologically innovative and reflexive approach to discourse analysis in education.